Entrepreneurial propensity in Pakistan and UK: A comparative study of Pakistani and UK prospective teachers - Ali Akhtar; Keith Topping; Riaz H. Tariq; Peter Wakefield (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2011)
This research compares entrepreneurial inclination of Pakistani and UK primary level prospective teachers (B.Ed. students). Factor analysis revealed entrepreneurial intentions, instrumental readiness and self-efficacy as three common factors among both the data sets. Both the groups of respondents were also compared on five conceptual variables namely locus of control, self efficacy, entrepreneurial intentions, instrumental readiness and subjective norms. The prospective teachers from UK were found to be significantly lower on instrumental readiness and entrepreneurial intentions than their Pakistani counterparts. There were some partial impacts of demographic variables on entrepreneurial propensity of both the groups of respondents. Some implications for planning and policy were outlined.
Keywords: 330; University; Survey; Entrepreneurial inclinations; Prospective teachers; Teacher training